Oil palm in Colombia: december 2023 - Federación Nacional de Cultivadores de Palma de Aceite, Fedepalma. (Federación Nacional de Cultivadores de Palma de Aceite, Fedepalma., 2024)
It is the most productive oilseed on earth; one planted hectare produces between 6 and 10 times more oil than other oilseeds. Colombia is the fourth-largest producer of palm oil globally and the first in the Americas.
Keywords: Aceite de palma; Palma de aceite; Producción; Sostenibilidad; Estadísticas